2020
DOI: 10.9734/ajess/2020/v8i130209
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in Relation to Academic and Clinical Performance of Dentistry Students

Abstract: Aims: This study sought to identify the level of creativity of dentistry students, to determine if there is a relationship between creativity and academic performance of dentistry students, and to determine if there is a relationship between creativity and clinical performance of dentistry students. Study Design:  Descriptive-Correlation Cross-sectional Study. Place and Duration of Study: Adventist University of the Philippines College of Dentistry, between May 2015 and April 2016. Methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…However, the modules on the market only focus on drills and revisions and are exam-oriented only (Hassan & Osman, 2016). Some studies have shown no significant difference in inventive thinking between treatment and control groups (Chifamba & Wijaya, 2020;Lay & Osman, 2020). Compared with traditional learning, the process of designing artifacts or products in a project takes a longer time (Osman & Lay, 2020;Penuel, 2019;Weitze, 2021).…”
Section: / 15mentioning
confidence: 99%
“…However, the modules on the market only focus on drills and revisions and are exam-oriented only (Hassan & Osman, 2016). Some studies have shown no significant difference in inventive thinking between treatment and control groups (Chifamba & Wijaya, 2020;Lay & Osman, 2020). Compared with traditional learning, the process of designing artifacts or products in a project takes a longer time (Osman & Lay, 2020;Penuel, 2019;Weitze, 2021).…”
Section: / 15mentioning
confidence: 99%